PENGARUH BRAND PERSONALITY PADA BRAND TRUST, BRAND ATTACHMENT, BRAND COMMITMENT, DAN BRAND LOYALTY - Yana Anggi Sabrina; Siti Khoiriyah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
This study aims to examine the effect of brand personality on brand trust, brand attachment, brand commitment and brand loyalty. Structural Equation Modeling (SEM) is used as analytical method. This study used purposivesampling techniques for sampling, as many as 230 young people aged 18-21 years old who live in Surakarta and intends to be loyal to soft drink Coca-Cola brand. This study shows positive effect brand personality tobrand trust, brand commitment and brand loyalty; positive effect brand trust to brand attachment; positive effect brand attachment to brand commitment; positive effect brand commitment to brand loyalty; brandpersonality has no effect to brand attachment, and brand trust has no effect tot brand loyalty. Object of this study is limited to soft drink Coca-Cola brand with a limited range of research areas in the city of Surakarta.Future studies are expected to conduct research with two objects at once, such as Coca-Cola and Pepsi or Coca-Cola and Nike.Implications of this study is the increased knowledge about the influence of brandpersonality on brand trust, brand attachment, brand commitment, and brand loyalty, so that The Coca-Cola Company and Coca-Cola marketer can determine the appropriate policy to guide and strengthen lastingrelationships between brands with consumers.Key words: Brand, brand personality, trust, attachment, commitment, and loyalty.